UPAYA MENINGKATAN PENGETAHUAN DAN PENGEMBANGAN USAHA MIKRO KECIL MENENGAH DI ERA DIGITALISASI DI DESA TELUK KECAMATAN LABUAN - Hani Muflihah; Rosihan Anwar (Jurnal Abdimas Bina Bangsa, 2023)
Micro, Small and Medium Enterprises, often abbreviated as MSMEs, are small-scale independent community economic activities whose management is carried out by community groups, families or individuals. MSMEs have an important role in the economy because they can create jobs, encourage economic growth, and promote entrepreneurship. Digitalization often aims to increase productivity, save time, and facilitate easier access to information and services. Digitalization is an important need for MSMEs to survive in increasingly fierce competition. Implementing digital transformation can increase operational efficiency, revenue, and change organizational culture to be more adaptive to change. The Community Service Program method is divided into 3 main stages. Stage 1 is the survey and socialization stage, stage 2 is the implementation of activities and stage 3 is evaluation. This research focuses on strategies implemented to increase knowledge and development of Micro, Small and Medium Enterprises (MSMEs) in Teluk Village in the era of digitalization. The aim is to analyze how the application of digital technology can be a catalyst in the growth of MSMEs and its impact on the local economy. Research methods involve surveys and interviews. The research results highlight the importance of digital training, access to online platforms, and collaboration between stakeholders, such as government, business people and academics. These findings illustrate that digitalization not only allows MSMEs to reach a wider market, but also encourages innovation and operational efficiency. Through an in-depth understanding of these dynamics, this study provides valuable guidance for decision makers at local and national levels to support the sustainable growth of MSMEs in the digital era.